71.2: Mechanical Characteristics of Flexible AMOLED Display. Issue 1 (June 2015) - Chen, Ji‐Feng; Tu, Chia‐Hsun; Lin, Po‐Yang; Hsu, Ming‐Chang; Huang, Chen‐Shuo; Hwu, Keh‐Long; Lu, Hsueh‐Hsing; Chang, Lee‐Hsun; Lin, Yu‐Hsin
Abstract : This paper investigates experimentally the mechanical reliability of AMOLED flexible display for the purpose of building feasible design concept for flexible products in the future. Three mechanical tests have been implemented respectively to investigate the mechanical strain limits of functional thin films, the electrical properties of TFT, and the mechanical reliability under bending process. Firstly, we find the tensile‐strain limit is strongly related to the total thickness of consecutive brittle inorganic layers such as silicon nitride film. Secondly, the mobility of the TFT made of LTPS increases as the channel is parallel to the bending direction whereas decreases as the channel is perpendicular to the bending direction. Besides, the threshold voltage is nearly unchanged during the bending test. Thirdly, the AMOLED panel and TFT can survive after 1000, 000 times of bending cycles, the AMOLED panel is not damaged under compressive strain up to −0.36%.